Studi Literatur Analisis Malware Menggunakan Metode Analisis Dinamis dan Statis - Rezki Syaputra; Syaifudin (Institute of Information Technology and Social Science (IITSS), 2020)
Malware is software or software created to infifiltrate or damage computer systems. The spread of malware today is so easy either through a USB flash drive, certain advertisements on websites, and other media. Everything is very closely related to crime such as theft of files, credit cards, internet banking and so forth. In this regard, there is a field that deals with crime namely digital forensics. One of the stages in digital forensics is analyzing digital evidence, in this case malware. To prove a piece of software, it is said that malware is knowing how the program works on a computer system. The Dynamic and Static Malware Analysis Method is a combination of methods that are suitable for analyzing how malware works. Based on an analysis of the workings of malware (poison ivy), it can be concluded that there are several signatures, fifile names, and strings that have been investigated in fact can be able to log in remotely without being noticed by the computer owner.